Financial performance analysis of IT and telecom companies in the Dhaka Stock Exchange - Afroz, Sadia (BRAC University, 2014)
This thesis is restricted.This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.